TV formats in anglophone Africa: The hegemonic role of South Africa in the TV format value chain. (1st March 2017) - Ndlela, Martin N.
This article examines the television format business in anglophone Africa using a global value chains (GVCs) approach. Examining the format chain value structures and considering the different input and output activities in the global TV-format chain, this article identifies South African media industries as the most dominant players in anglophone Africa. Their dominance is manifested in the different stages of the value chain, from acquisition of format rights to broadcasting of finished programmes to different market segments in the region. This article argues that South Africa's hegemonic status in the format value chain can be attributed to the formal nature of its creative industries and their configurations within the global/local matrix. South media corporations are embedded into the global media system through their business structures, capital investments, ownership, partnership and strategic alliances. At local level, South African companies have expanded into various African markets. This hegemony is contrasted with countries like Nigeria, who despite being the biggest producer of audio-visual material in Africa, is less active in the global format value chains.